Resistance exercise training increases skeletal muscle mitochondrial respiration in chronic obstructive pulmonary disease - Laura Oberholzer; Knut Sindre Mølmen; Daniel Hammarström; Gunnar Slettaløkken Falch; Anne‐Kristine Meinild Lundby; Bent R. Rønnestad; Stian Ellefsen; Carsten Lundby (Wiley, 2022)
Abstract Background Chronic obstructive pulmonary disease (COPD) is associated with skeletal muscle mitochondrial dysfunction. Resistance exercise training (RT) is a training modality with a relatively small pulmonary demand that has been suggested to increase skeletal muscle oxidative enzyme activity in COPD. Whether a shift into a more oxidative profile following RT also translates into increased mitochondrial respiratory capacity in COPD is yet to be established. Methods This study investigated the effects of 13 weeks of RT on m. vastus lateralis mitochondrial capacity in 11 persons with moderate COPD [45% females, age: 69 ± 4 years (mean ± SD), predicted forced expiratory volume in 1 s (FEV1): 56 ± 7%] and 12 healthy controls (75% females, age: 66 ± 5 years, predicted FEV1: 110 ± 16%). RT was supervised and carried out two times per week. Leg exercises included leg press, knee extension, and knee flexion and were performed unilaterally with one leg conducting high‐load training (10 repetitions maximum, 10RM) and the other leg conducting low‐load training (30 repetitions maximum, 30RM). One‐legged muscle mass, maximal muscle strength, and endurance performance were determined prior to and after the RT period, together with mitochondrial respiratory capacity using high‐resolution respirometry and citrate synthase (CS) activity (a marker for mitochondrial volume density). Transcriptome analysis of genes associated with mitochondrial function was performed. Results Resistance exercise training led to similar improvements in one‐legged muscle mass, muscle strength, and endurance performance in COPD and healthy individuals. In COPD, mitochondrial fatty acid oxidation capacity and oxidative phosphorylation increased following RT (+13 ± 22%, P = 0.033 and +9 ± 23%, P = 0.035, respectively). Marked increases were also seen in COPD for mitochondrial volume density (CS activity, +39 ± 35%, P = 0.001), which increased more than mitochondrial respiration, leading to lowered intrinsic mitochondrial function (respiration/CS activity) for complex‐1‐supported respiration (−12 ± 43%, P = 0.033), oxidative phosphorylation (−10 ± 42%, P = 0.037), and electron transfer system capacity (−6 ± 52%, P = 0.027). No differences were observed between 10RM and 30RM RT, nor were there any adaptations in mitochondrial function following RT in healthy controls. RT led to differential expression of numerous genes related to mitochondrial function in both COPD and healthy controls, with no difference being observed between groups. Conclusions Thirteen weeks of RT resulted in augmented skeletal muscle mitochondrial respiratory capacity in COPD, accompanied by alterations in the transcriptome and driven by an increase in mitochondrial quantity rather than improved mitochondrial quality.